Monoclonal Antibody-based Immunoassays for the Specific Quantitation of Rat PAI-1 Antigen and Activity in Biological Samples - Ngo, Thu-Hoa; Verheyen, S.; Knockaert, I.; Declerck, P. J. (Thrombosis and Haemostasis, 1998)
Two enzyme-linked immunosorbent assays (ELISAs) for the quantitation of rat plasminogen activator inhibitor-1 (PAI-1) antigen and activity, respectively, in biological fluids were developed using monoclonal antibodies raised against recombinant rat PAI-1. These assays had a lower limit of sensitivity in plasma of 0.3 and 0.15 ng/ml, respectively. The intra-assay, inter-assay and inter-dilution coefficients of variation were 9, 14 and 9%, respectively, for the antigen assay and 8, 17 and 13%, respectively for the activity assay. Assay recoveries of recombinant rat PAI-1 (5 to 20 ng/ml) added to plasma were 73 to 88% and 89 to 93% for the antigen and the activity assay, respectively. The level of PAI-1 antigen in rat plasma was 1.8 ± 0.9 ng/ml (mean ± SD, n = 18), with a corresponding value of 1.0 ± 0.5 ng/ml for PAI-1 activity. In lysed platelet-rich rat plasma PAI-1 antigen was 6.0 ± 1.0 ng/ml (n = 8) and PAI-1 activity was 2.3 ± 0.4 ng/ml (n = 8). Endotoxin injection (0.5 mg/kg) induced a time-dependent increase of both PAI-1 antigen and PAI-1 activity levels in rat plasma, eventually resulting in a 100- to 200-fold increase (p <0.0001 vs. baseline). A linear correlation was found between PAI-1 antigen and activity levels in normal plasma (r = 0.63, n = 18, p <0.01) and in plasma from endotoxin-treated rats (r = 0.90, n = 35, p <0.001). Application of these assays for the analysis of gel filtration experiments of plasma from endotoxin-treated rats demonstrated that PAI-1 antigen eluted as two peaks (with corresponding Mr of ~430 kDa and 61 kDa) whereas PAI-1 activity eluted as a single peak corresponding with the high molecular weight antigen form.Thus, these unique assays allowing the specific determination of rat PAI-1 antigen and rat PAI-1 activity may constitute important tools for further investigations on the pathophysiological role of PAI-1 in a variety of experimental rat models.